Deoxyshikonin isolated from Arnebia euchroma inhibits colorectal cancer by down-regulating the PI3K/Akt/mTOR pathway - Yuzhen Zhu (Taylor & Francis Group, 2019)
Context: Shikonins, a series of natural occurring naphthoquinones extracted from Arnebia euchroma (Royle) Jonst. (Boraginaceae), have antitumor activities and low toxicity. Objective: To illuminate potential activity and mechanism of shikonins against colorectal cancer (CRC). Materials and methods: Five shikonins were isolated from A. euchroma, and elucidated by extensive spectroscopic analysis. Anti-proliferative activities of shikonins (0–100 μg/mL) on human colorectal cells were evaluated by MTT and CCK-8 for 24 or 48 h. Cell apoptosis and cycle distribution were examined by FCM analysis. The expression of PI3K/Akt/mTOR pathway mRNAs and proteins was analysed by RT-PCR and Western blot, respectively. Cell viability, cell apoptosis, cell cycle and protein expression were measured, when co-treated with PI3K/Akt/mTOR pathway inhibitors. The in vivo activity of deoxyshikonin was evaluated using xenograft tumour model. Results: Deoxyshikonin and another four shikonins were isolated and identified. Deoxyshikonin exhibited anti-proliferative activity with IC50 of 10.97 μM against HT29 cells. Moreover, the percentage of early apoptotic cells and G0/G1 cells increased from 1 to 29% and 44 to 67% with 0–50 μg/mL deoxyshikonin, respectively. Deoxyshikonin also down-regulated the expression of PI3K, p-PI3K, Akt, p-Akt308 and mTOR proteins in HT29 and DLD-1 cells. Moreover, LY294002, NVP-BEZ235 and MK-2206 can make deoxyshikonin more cell proliferation inhibited, cell cycle arrested at G0/G1 and apoptosis promoted. In vivo study, the weight of tumour tissues at deoxyshikonin groups was significantly reduced compared with the control group, and PI3K, p-PI3K, Akt, p-Akt308 and mTOR expression was decreased. Discussion and conclusions: We can conclude that deoxyshikonin isolated from Arnebia euchroma inhibited CRC through the PI3K/Akt/mTOR pathway.